Reflection of the superior court of justice's jurisprudence on personal searches in Military Police activity (Research, Society and Development, 2025)
The police stop is the most common point of contact between the Military Police and the citizen. It is carried out as a preventive action based on reasonable suspicion and police intuition. Grounded in Article 244 of the Brazilian Code of Criminal Procedure (CPP), this procedure is conditioned upon the existence of reasonable suspicion that the individual is in possession of illicit objects, prohibited weapons, or evidence related to crimes. The general objective of this study was to analyze, through legal doctrine and jurisprudence, the impacts of the Superior Court of Justice (STJ) decision on personal searches and police stops. The results indicate that, according to the STJ decision—specifically by its Sixth Panel—personal or vehicle searches without a judicial warrant, based solely on the officer’s subjective impression of a person’s appearance or behavior, are deemed illegal. After reviewing the relevant legislation, legal doctrine, and jurisprudence, it is clear that this decision significantly hinders the actions of the Military Police, considering that the technical aspects of the stop—taught during training and specialization—are based on behavioral traits and operational experience. Nonetheless, experience cannot replace proper training, which serves as a foundation for the recurring interventions of the Military Police.